If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -143 = -127 Reorder the terms: -143 + 8x = -127 Solving -143 + 8x = -127 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '143' to each side of the equation. -143 + 143 + 8x = -127 + 143 Combine like terms: -143 + 143 = 0 0 + 8x = -127 + 143 8x = -127 + 143 Combine like terms: -127 + 143 = 16 8x = 16 Divide each side by '8'. x = 2 Simplifying x = 2
| 9n-26=9+4n | | 436x-789=-571 | | 23x^2-20=0 | | -13x+28=-11 | | Y^2-.6y+.1=0 | | Y^2-.6y+.1111111111=0 | | 6x+18=4x+2 | | 3b(4-2b)-6b=-b(6b+7)+104 | | 12x+(-18)=66 | | -5x+13=58 | | 2.1(3y+1)-1.8=1.7(7y-8)-2.9 | | 3x-5=2x-9 | | y=-12+6x | | -2x+6=2 | | 4x^4-36x^2+9=0 | | y=6x-12 | | 7y^2-y+3=0 | | x^4-8x^2+13=0 | | -3x-11=4 | | 3x-5=64 | | 2r^2-98=0 | | 12n+112=1000 | | 3x-8+28=180 | | v^2+3v-28=0 | | 0=-8t^2+20t | | -3x+1=-1-2x | | 7=5x-2 | | 60=6y | | x^3+10x^2+41x+50=0 | | 3a^2-6a=0 | | 5-0.6k=5 | | 8x-1=9+9x |